Solving cracking phenomenon in premium transparent toilet soap production using Stretched LLDPE Film Wrap - Mat Sharif, Zainon; Mohd Taib, Norhasnina; Yusof, Mohd Sallehuddin; Rahim, Mohammad Zulafif; Mohd Tobi, Abdul Latif; Othman, Mohd Syafiq (IOP Publishing, 2017)
Cracking phenomenon in soap production is an imminent problem. It renders the soap aesthetically unpleasing. This study attempts to find best solution to solve cracking phenomenon in premium soap production. The adopted approach is a stamping method with stretched LLDPE wrap film. The result shows that stretched LLDPE wrap film able to solve the cracking problem. The appearance of the premium transparent was improved. This paper presents the results and the SOP for stretched LLDPE film wrap for soap making industries to adopt.